Modeling of reconstuction of the coracoclavicular ligament in cases of injuries of the acromioclavicular joint - Zabielin, Ivan; Golovakha, Maksim; Shishka, Igor; Choporov, Sergey; Gomenuk, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2014)
Objective: to build a model of reconstruction of the coracoclavicular ligament in cases of the acromioclavicular joint injuries and to determine the position of point for the fixateur on the clavicle ensuring minimal forces in the artificial ligament. Model of the acromioclavicular joint represented as a system of interacting rigid rods was taken as a basis. As a result of this study of equilibrium of the system there was obtained a formula allowing to determine the position of point for the fixateur on the clavicle which corresponds to minimal reaction of footing (tensile force) in the fixateur. Channel position in the clavicle for mounting of the fixateur depends on its length. Therefore the most favorable point for the channel in the acromial end of the clavicle has to be located at a distance from 12.9 up to 15.5 % of its total length.